2019
DOI: 10.1108/tlo-08-2018-0139
|View full text |Cite
|
Sign up to set email alerts
|

Moderating role of innovation culture in the relationship between organizational learning and innovation performance

Abstract: Purpose Different studies have analyzed the relationship between organizational learning (OL) and innovation performance (IP). However, the question of how innovation culture (IC) affects the relationship between OL and IP remains unexplored. This study aims to examine the impact of IC on the relationship between OL and various dimensions of IP, including product, process and objective innovation. Design/methodology/approach A research model was developed and performed based on the relevant literature in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 56 publications
5
58
0
7
Order By: Relevance
“…This study revealed that the outcome of H4 is significant at a 0.05 level of significance (β = 0.040, t = 2.221, p < 0.027), and thus, H4 is supported. This result further confirmed previous studies that have demonstrated the decisive role of innovation culture as an intervening variable that develops organizational performance (Alosani et al, 2020;Ghasemzadeh et al, 2019) and an internal environment that improves employee work behavior to learn and innovate continuously.…”
Section: Discussion Of the Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…This study revealed that the outcome of H4 is significant at a 0.05 level of significance (β = 0.040, t = 2.221, p < 0.027), and thus, H4 is supported. This result further confirmed previous studies that have demonstrated the decisive role of innovation culture as an intervening variable that develops organizational performance (Alosani et al, 2020;Ghasemzadeh et al, 2019) and an internal environment that improves employee work behavior to learn and innovate continuously.…”
Section: Discussion Of the Findingssupporting
confidence: 91%
“…Hence, more studies should measure the impact of TQM practices on SMEs' performance and should not stop with the results extracted from studies applied on large firms (Sahoo & Yadav, 2020;Sila, 2018). Studies have also suggested that innovation culture does not directly affect their performance and should play a conditional role (Ghasemzadeh et al, 2019).…”
Section: Organizational Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Many scholars said that innovation is a key instrument for facing an uncertain business environment [7] that recognize innovation is very crucial in a complex environment [22,23] and important in determining sustainability role in success and survival [24].…”
Section: B Innovationmentioning
confidence: 99%
“…En este sentido, la comunicación, la presencia de una estrategia de innovación, la participación de los colaboradores en procesos de intercambio de conocimiento y comunidades de práctica son elementos fundamentales en la innovación empresarial (Díaz et al, 2014;González et al, 2014;Bravo y Herrera, 2009). Puntualmente, la cultura de innovación se define como la atmósfera multidimensional de valores y creencias compartidas por los equipos que los hacen propensos a explorar nuevas oportunidades y conocimientos para innovar (Naranjo y Calderon, 2018; Dabić et al, 2019;Ghasemzadeh et al, 2019). Este tipo de culturas son impulsadas por 4 aspectos fundamentales: liderazgo, recursos, gestión del conocimiento y procesos (Dobni y Klassen, 2020).…”
Section: Estrategia Y Cultura De Innovaciónunclassified